Lúdica y motivación infantil - Guanochanga Chilig, Alexandra Margoth (2016)
The present proyect of playful and child motivation is based on the school environment to form critical and irreplaceable human beings, the objective was treaty for comprehensive development of children’s the institution Private School "Federico Froebel" for learning must be constructive and qualitative methodology, determining possible problems in students, as it investigates the needs of infants to help improve children's motivation in the classroom and the playful in the significant learning of them. The information was processed statistically tabulated and displayed in tables and graphs. With their analysis and interpretation helped link the problem, the objectives, scientific substantiation and variables with the conclusions and recommendations. Also as a basic principle we consider a basic and important concept that games must be based on educational content to help develop the habits, skills and positive attitudes in school work, applying the reasoning and cognitive development encouraging students to student using thinking strategies that promote exchange views promoting cooperation and communication in the teaching process - learning. The success in learning depends on good planning of activities to promote the construction of concepts, starting concrete experiences, interaction with others promoting their humanist character of collaboration and mutual trust on the part of teachers and párvulos.